On the effective property of a micro-cracked and a microscopically curved interface between dissimilar materials - Fan, Hui (2023)
Two different types of imperfect interfaces between dissimilar elastic materials under antiplane deformations are studied using micromechanics concepts. Interfaces containing interfacial micro-cracks and those that are microscopically wavy (sinusoidal) are modeled as spring-like and membrane-like respectively at the macroscopic level. The strain energy in the microscopic configuration is equated to that in the macroscopic configuration in order to estimate the effective properties of the imperfect interfaces. The boundary value problems for computing the strain energy at the microscopic level are formulated and solved by using boundary integral equations.